THE APPLICATION OF OKRE (Overview, Key Ideas, Reviewing and Evaluation) IN IMPROVING STUDENTS’ READING COMPREHENSION AT SMK MUHAMMADIYAH 2 BONTOALA MAKASSAR - Midayani; St. Asriati AM; Eka Prabawati Rum (Journal of Language Testing and Assessment, 2021)
This inquire about pointed to discover out the impact of OKRE Method on understudies perused comprehension that center on level of strict and interpretative of comprehension.”“The analyst connected prel – experimental method with one bunch pre – test and post – test.”“The test of this inquirel about was courser XI Accounting of SMK Muhammadiyah 2 Bontoala Makassar which comprised of 30 understudies.”“The test was taken by utilized purposive inspected method.”“The research findings showed that the tenth grade of Accounting SMK Muhammadiyah 2 Bontoala Makassar had Fair score in pre-test. After given treatment their reading comprehension was significantly improved. The result of the inquired about were the cruel score of pre – test in Exacting (Fundamental Thought) score pre – test was 58.6 and post – test was 86.56. in grouped of detail the score of pre – test was 56.4 and post – test was 92.6 with t – test esteem Exacted is more prominent than t – table (13.26 > 2.45).”“Cruel score of interpretative in pre – test was 63.63 and post – test 82 with the t – test exteem is more prominent that t – table (8.34 >2.45).”“The result of calculated t – test of the pointers within the students’ t – test (Exacted and interpretative) was more prominent than t – table 21.60 > 2.45.”“It implies that there was noterworthiness diverse between some time recently and after gived the treatment.”“It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded that the use of OKRE Influence the students’ reading comprehension.”